Pengaruh Variasi Komposisi Amilosa terhadap Kemudahan Biodegradasi Poliuretan - Eli Rohaeti; N. M. Surdia; Cynthia L. Radiman; E. Ratnaningsih (Jurnal Matematika & Sains, 2003)
Amylose had been used to synthesize polyurethanes. A mixture of polyethylene glycol (PEG) with a molecular weight 400 with amylose was reacted with diphenylmethane-4,4â-diisocyanate (MDI) at room temperature to produce polyurethanes. The precured polyurethanes were heat-pressed and PU sheets were obtained. Characterization of functional groups was determined by FTIR spectrophotometry and crystallinity was analyzed by using XRD. The hydrogen bonding index (HBI) of polyurethane samples increased with an increasing of amylose content. The addition of 15% (w/w) amylose decreased the degree of crystallinity of polyurethane. The films of polyurethanes were biodegraded by Pseudomonas aeruginosa in an liquid of Luria Bertani (LB) media at 37oC for 5, 10, 15, 20, 25, and 30 days, with the changing of media every 5 days. The result of weight loss percentace showed that all polymers may be biodegraded, with different biodegradation rate. The biodegradability (rate of weight loss) of polyurethanes by Pseudomonas aeruginosa increased when the amylose content in the polyurethane increased. The polyurethane product with 15% amylose â PEG400 â MDI had the highest biodegradability.